A Mechanistic Probe into the Dual Inhibition of T. cruzi Glucokinase and Hexokinase in Chagas Disease Treatment – A Stone Killing Two Birds?. Issue 2 (26th January 2021) - Omolabi, Kehinde F.; Odeniran, Paul O.; Olotu, Fisayo A.; Soliman, Mahmoud E. S.
Abstract: Glucokinase (GLK) and Hexokinase (HK) have been characterized as essential targets in Trypanosoma cruzi ( Tc )‐mediated infection. A recent study reported the propensity of the concomitant inhibition of Tc GLK and Tc HK by compounds GLK2‐003 and GLK2‐004, thereby presenting an efficient approach in Chagas disease treatment. We investigated this possibility using atomic and molecular scaling methods. Sequence alignment of Tc GLK and Tc HK revealed that both proteins shared approximately 33.3 % homology in their glucose/inhibitor binding sites. The total binding free energies of GLK2‐003 and GLK2‐004 were favorable in both proteins. PRO92 and THR185 were pivotal to the binding and stabilization of the ligands in Tc GLK, likewise their conserved counterparts, PRO163 and THR237 in Tc HK. Both compounds also induced a similar pattern of perturbations in both Tc GLK and Tc HK secondary structure. Findings from this study therefore provide insights into the underlying mechanisms of dual inhibition exhibited by the compounds. These results can pave way to discover and optimize novel dual Tc inhibitors with favorable pharmacokinetics properties eventuating in the mitigation of Chagas disease. Abstract :